LOS ESTUDIOS CULTURALES EN HONDURAS: LA BÚSQUEDA DE ALGUNAS FUENTES CULTURALES PARA LA RECONSTRUCCIÓN DEL IMAGINARIO NACIONAL HONDUREÑO. - Amaya, Jorge Alberto (2006)
This article provides a balance that shows that the Honduran cultural history is still to be written. In this manner, it evaluates the fact that fields of study such as the building of a nation and the national identity, abundant in other countries, are scarce and fragmentary in the case of Honduras, with some exceptions.